Significance of evaluating mandibular parameters for the identification of an individual - Jain, Ayushi; Sharma, Pooja; John, Sharon; Gupta, Shalini; Dewan, Rakesh (International Journal of Research in Medical Sciences, 2024)
Background: Estimating the age of death is a crucial step since it narrows the field of probable identities that must be compared to remains after mass tragedies. Morphological changes in the mandible are mostly driven by an individual’s age and occlusal status. The aim of this study was to determine the association of the dimensions of these parameters with the age and gender of an individual with a larger sample size using orthopantograms in the north Indian population. Methods: A retrospective radio morphometric analysis was performed for panoramic radiographs of 300 (150 males and 150 females). The digital panoramic images were saved in Dicom format and exported to MicroDicom software for linear measurements. The co-relation of study parameters with age was analyzed by one-way ANOVA and assessment of co-relation with sex by applying student’s t-test. Results: The mean values of the right and left gonial angles were higher in females, while the ramus height and bigonial width dimensions were greater in males. However, only the left gonial angle and ramus height showed statistically significant differences with gender (p<0.05). Conclusions: The present study found substantial changes in gonial angle, ramus height, and bigonial breadth based on gender and age in a larger sample size. As a result, these dimensions can be an accurate predictor of an individual’s age and sex. Thus, morphometric examination of the mandible can be a useful tool in both identifying individuals and studying growth patterns.